Pitfalls of Cooperatives: Framework for Effective Management: Qualitative Evidence from Developing Countries - Khanal, Khageshyor (KIC International Journal of Social Science and Management, 2023)
This qualitative research investigates the difficulties of cooperatives in Nepal, concentrating on governance, management, and financial sustainability. The study used deliberate sampling to identify thirteen cooperative managers in Kathmandu, Nepal, as participants. Semi-structured interviews were performed, using an interview guide consisting of open-ended questions covering major topics such as challenges, decision-making processes, organizational structure, financial management, and sustainability plans. The sample size was set based on data saturation to ensure complete data collection. Thematic analysis was used to analyze the transcribed interviews, which included systematic data coding using a mix of deductive and inductive coding approaches. The investigation found recurring mistakes and obstacles in cooperative governance, management, and financial sustainability. To enhance legitimacy, direct quotes from participants were used. The results emphasize the need of resolving governance concerns, enhancing communication and dispute resolution within cooperatives, and adopting good financial management practices. The research adds to the current literature by offering framework and insights into the unique issues encountered by cooperatives in Nepal and making suggestions to improve their sustainability.